The Significance of Nepal’s Geopolitical Location; Reality Checking - Adhikari, Sandip (Unity Journal, 2024)
This research paper investigates Nepal's geostrategic importance by analyzing its role as a significant nexus in South Asia. In ancient times, Nepal occupied a crucial geostrategic position as it served as a pivotal crossroads connecting South Asia, Tibet, and China, facilitating the exchange of commodities, ideas, and culture. The central argument posits that Nepal's geographic location endows it with substantial strategic significance, both politically and economically, enabling it to influence regional dynamics. Employing a mixed methodology, the research delves into various facets of Nepal's geostrategic relevance through historical assessments, geopolitical analyses, and case studies of hydro-politic potentiality. The approach commences by examining Nepal's historical role as a buffer state amid regional powers, leading to a longstanding history of diplomatic struggles to safeguard its sovereignty. Furthermore, the paper explores how Nepal's geographical position shapes its security dynamics, particularly in the context of the escalating China-India rivalry in contemporary times, employing geopolitical frameworks to illuminate this aspect. To shed light on Nepal's involvement in facilitating global trade and connectivity, the methodology also includes case studies of infrastructure initiatives such as the Belt and Road Initiative and regional connectivity projects. In conclusion, the paper asserts that Nepal's geostrategic significance is a product of its historical development and proactive international relations, closely intertwined with its geographic positioning. It underscores Nepal's potential to serve as a conduit for regional cooperation and economic integration while emphasizing the need for astute navigation to preserve its independence in a challenging geopolitical landscape.